Reproducibility of Echocardiograph-Derived Multilevel Left Ventricular Apical Twist Mechanics - Stewart, G.; Yamada, A.; Kavanagh, J.; Haseler, Luke; Chan, J.; Sabapathy, S. (2016)
© 2015, Wiley Periodicals, Inc. Left ventricular (LV) twist mechanics are routinely assessed via echocardiography in clinical and research trials investigating the function of obliquely oriented myocardial fibers. However, echocardiograph-derived measures of LV twist may be compromised by nonstandardized acquisition of the apical image. This study examined the reproducibility of echocardiograph-derived parameters of apical twist mechanics at multiple levels of the apical myocardium. Two sets of 2D LV parasternal short-axis images were obtained in 30 healthy subjects (24 men; 19-57 year) via echocardiography. Images were acquired immediately distal to the papillary muscles (apical image 1), immediately above the point of LV cavity obliteration at end systole (apical image 3), and midway between apical image 1 and apical image 3 (apical image 2). Repeat scans were performed within 1 hour, and twist mechanics (rotation and rotation rate) were calculated via frame-by-frame tracking of natural acoustic echocardiographic markers (speckle tracking). The magnitude of apical rotation increased progressively toward the apex (apical image 1: 4.2 ± 2.1, apical image 2: 7.2 ± 3.9, apical image 3: 11.8 ± 4.6). apical images 1, 2, and 3 each had moderate to good correlations between repeat scans (ICC: 0.531-0.856). When apical images 1, 2, and 3 were averaged, rotation was 7.7 ± 2.7 and between-scan correlation was excellent (ICC: 0.910). Similar results were observed for systolic and diastolic rotation rates. Averaging multiple standardized apical images, tending progressively toward the apex, generated the most reproducible rotation indices and may be optimal for the assessment of LV twist mechanics across therapeutic, interventional, and research studies; however, care should be taken given the influence of acquisition level on the magnitude of apical rotation.